ASSESSMENT METHODS OF EFFECTIVENESS OF UNEMPLOYABLE POPULATION SOCIAL POLICY ON THE BASIS OF INTEGRATED QUALITY OF LIFE - Задорожний, Г. В.; Діденко, Ю. Ю. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The article analyzes the informational and methodological problems of objective estimation of social policy effectiveness. It is proposed to evaluate the social policy effectiveness basing on multi-level system of social indicators that can be used while calculating life quality integral indicator of the selected.